ChemInform Abstract: Gold(I) or Silver Catalyzed Synthesis of α‐Indolylacrylates. Issue 51 (17th December 2013) - Pirovano, Valentina; Facoetti, Diego; Dell'Acqua, Monica; Fontana, Emanuela Della; Abbiati, Giorgio; Rossi, Elisabeth
Abstract The reaction of 2‐substituted indoles with 2‐acetamidoacrylate can be catalyzed by Au(I) or Ag(I) salts to afford the title compounds in good to moderate yields.